Hypotermi vid anestesi av hund - Bremholt, Therése (2009)
The reasons for hypothermia during general anaesthesia are many and varied. The lowered body temperature causes negative physiological effects and leads to discomfort for the animal during the recovery period. This student report is a combination of field study and literature review. In the field study the changes in ambient temperature and the rectal temperature of dogs were monitored during general anaesthesia. The purpose of the study was to see if the body temperature of dogs was reduced during general anaesthesia. In the literature review the basic causes for hypothermia are addressed as well as the consequences of the condition. Further more the dog’s thermoregulation and monitoring are discussed as well as different methods for preventing and treating hypothermia. The purpose of this student report has been to get a better understanding of hypothermia, its causes, consequences and treatment. I hope to highlight the necessity for the nursing of dogs during general anaesthesia.